Theoretical study of separation of dehumidification and cooling in air conditioning systems - Ong, Jun Xiong (2015)
The increase in energy prices and global warming effects has raised the concern of reducing energy consumption. In countries with hot and humid climate like Singapore, the dehumidification process makes air conditioning (A/C) systems very energy intensive. In Singapore, A/C systems accounts for about 50% of the power consumption in most buildings. To reduce the drawback of A/C systems, the separation of dehumidification and cooling in A/C systems has been introduced. In this project, theoretical studies are carried out to analyse the effectiveness of the separation of dehumidification and cooling in A/C systems via the desiccant dehumidification method, over a wide range of ambient and indoor air conditions, by determining the enthalpy of moist air at each of the points and the corresponding change in enthalpy between the points of interest. For the desiccant dehumidification method, Silica gel is chosen as the desiccant material as it is reusable via heating. Results for the change in enthalpy of moist air show that the separation of dehumidification and cooling in A/C systems is about 30% ~ 65% more effective than conventional air conditioning systems, over a wide range of operating conditions. Cost analysis shows that the separation of dehumidification and cooling in A/C system, as compared to the conventional air conditioning system, can reduce the electricity consumption cost by about 35% to 60%, which is consistent with the results from the theoretical calculations. The results from the various studies show that the separation of dehumidification and cooling in A/C system is more effective than, and a better alternative to, the conventional air conditioning system.